Mathematical Study on a Non-Darcian Flow of a Nanofluid - Sathyapriya, B.; Subha, M.; Sivasankari, S.; Ananthaswamy, V. (Journal of Applied Nonlinear Dynamics, 2026)
The flow of two dimensional Buogiorno nanofluid across an extending sheet having magnetic effect with a non-Darcy porous medium is explored analytically. By applying the transformation of similarity, the associated dimensional equations are simplified into dimensionless equations. With the aid of Ananthaswamy-Sivasankari approach and Modified Homotopy Analysis Technique, the expressions regarding the corresponding non-dimensional temperature, velocity, and concentration equations are attained. When the outcomes are compared to the numerical solution, a very excellent fit is found. Numerous controlling parameters including magnetic, porosity and thermophoresis are graphically depicted to reveal how they affect the flow. Furthermore, the physical parameters, especially the reduced number of Sherwood, and the reduced number of Nusselt are visually displayed.